A T4SS Effector Targets Host Cell Alpha-Enolase Contributing to Brucella abortus Intracellular Lifestyle - Marchesini, María I.; Morrone Seijo, Susana M.; Guaimas, Francisco F.; Comerci, Diego J. (Frontiers in Cellular and Infection Microbiology, 2016)
Brucella abortus, the causative agent of bovine brucellosis, invades and replicates within cells inside a membrane-bound compartment known as the Brucella containing vacuole (BCV). After trafficking along the endocytic and secretory pathways, BCVs mature into endoplasmic reticulum-derived compartments permissive for bacterial replication. Brucella Type IV Secretion System (VirB) is a major virulence factor essential for the biogenesis of the replicative organelle. Upon infection, Brucella uses the VirB system to translocate effector proteins from the BCV into the host cell cytoplasm. Although the functions of many translocated proteins remain unknown, some of them have been demonstrated to modulate host cell signaling pathways to favor intracellular survival and replication. BPE123 (BAB2_0123) is a B. abortus VirB-translocated effector protein recently identified by our group whose function is yet unknown. In an attempt to identify host cell proteins interacting with BPE123, a pull-down assay was performed and human alpha-enolase (ENO-1) was identified by LC/MS-MS as a potential interaction partner of BPE123. These results were confirmed by immunoprecipitation assays. In bone-marrow derived macrophages infected with B. abortus, ENO-1 associates to BCVs in a BPE123-dependent manner, indicating that interaction with translocated BPE123 is also occurring during the intracellular phase of the bacterium. Furthermore, ENO-1 depletion by siRNA impaired B. abortus intracellular replication in HeLa cells, confirming a role for α-enolase during the infection process. Indeed, ENO-1 activity levels were enhanced upon B. abortus infection of THP-1 macrophagic cells, and this activation is highly dependent on BPE123. Taken together, these results suggest that interaction between BPE123 and host cell ENO-1 contributes to the intracellular lifestyle of B. abortus.